A study on the relationship between service innovation and firm performance of logistic companies in Malaysia - M.Amin, Norseanti (2023)
The study's main objective is to examine the relationships between service innovation and firm performance through the mediating role of service quality among logistic firms. Empirical studies that analysed the innovation-performance relationship appear to focus on manufacturing firms. This brought questions about why service innovation analysis remains a less studied area where the central objective of the current study is to address this gap. The present study believes that service quality modifies the original relationships between service innovation and firm performance. In other words, the relationship between service innovation and firm performance depends on service quality. There is scarce research on service innovation and firm performance with the mediating effect of service quality in the Malaysian logistic industry. There is a need to exploit this knowledge. The current study tests four hypotheses built on existing theoretical models. The current study employed a structural equation model (SEM) with a PLS approach to achieve our research objectives and analyse the measurement and structural model. Three hundred self-administered questionnaires were returned, yielding a response rate of 30% using convenience sampling approach. The results show that service innovation significantly affects firm performance and service quality. Also, service quality has a significant effect on firm performance. The study found that service quality mediates the relationship between service innovation and firm performance. It can be derived from this study that firms should emphasise service innovation, as these innovations are found to be important instruments for achieving employee and customer satisfaction